A Critique and Review on the Book Endogenous Regional Development: Leadership and Institutions - Farhad Tarahomi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Endogenous Regional Development: Leadership and Institutions examines the role of the three components of leadership, institutions, and entrepreneurship in creating endogenous regional development. The main idea of the authors is that these three elements can provide the basis for the correct guidance of the two factors of resource endowment and adaptation to the market structure towards endogenous regional development. This statement is based on facts revealed in different parts of the world. The method of the present article in reviewing the book is documentary and analytical and the purpose is to evaluate the work with an emphasis on its content critique. The results of the study show that although the concepts contained in the book cover part of the scientific needs of the country, it has shortcomings such as not testing the proposed model, mentioning indicators that cannot be measured accurately, and using inappropriate criteria in measuring is one of the introduced indicators. In addition, a precise and specific definition of the region is not given. Furthermore, expressing the experiences of different regions, which makes up a large part of the book, lacks a general conclusion.